1974
DOI: 10.1107/s0021889874009745
|View full text |Cite
|
Sign up to set email alerts
|

A cryostat for collection of three-dimensional diffractometer data at liquid helium temperatures

Abstract: A beryllium-walled cryostat is described which allows collection of nearly a full sphere of accurate three-dimensional X-ray diffractometer data at liquid-nitrogen (LN2) and liquid-helium (LHe) temperatures. Cryogen consumption is 0.3-0.4 liters of LHe per hour at 30~K and 0.1-0.2 liters of LN2 per hour at 78 °K. The specimen is mounted on a copper block, the temperature of which is controlled to within 0.1 °. Measurements with a powder sample of TbVO4 show that at 33~JK the specimen temperature is within 2 ° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…A crystal specimen (1.58 x 10 -2 mm a in volume) was sealed in a thin-walled glass capillary and mounted on a Picker FACS-1 diffractometer at Buffalo. The crystal was cooled by a conduction-type cryostat, developed by Coppens et al (1974), to 80 + 1 K with liquid nitrogen. Intensity data were collected with Mo Ka radiation.…”
Section: Methodsmentioning
confidence: 99%
“…A crystal specimen (1.58 x 10 -2 mm a in volume) was sealed in a thin-walled glass capillary and mounted on a Picker FACS-1 diffractometer at Buffalo. The crystal was cooled by a conduction-type cryostat, developed by Coppens et al (1974), to 80 + 1 K with liquid nitrogen. Intensity data were collected with Mo Ka radiation.…”
Section: Methodsmentioning
confidence: 99%
“…A crystal, 0.25 x 0.24 x 0.27 mm, was sealed in a glass capillary and mounted in the cryostat described by Coppens, Ross, Blessing, Cooper, Larsen, Leipoldt, Rees & Leonard (1974).…”
Section: X-ray Experiments 81 Kmentioning
confidence: 99%
“…Therefore, this problem is especially acute for the shorter X-ray wavelengths, Mo Ka and Ag Ka. When using Mo or Ag X-ray tubes some authors prefer to use fl-filters rather than a monochromator (Coppens, Ross, Blessing, Cooper, Larsen, Leipoldt & Rees, 1974). The problem of inhomogeneity is believed to be less severe or even absent for Cu Ka radiation (Birknes & Hansen, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the distribution of intensity within the incident beam can be seriously affected when a monochromator is used (Coppens, Ross, Blessing, Cooper, Larsen, Leipoldt & Rees, 1974) and a correction procedure for the errors in single-crystal intensities due to the inhomogeneity of the incident beam has been developed and tested by Harkema, Dam, van Hummel & Reuvers (1980). The principal reason proposed to explain the inhomogeneity of the monochromated beam is the low monochromator diffraction angle.…”
Section: Introductionmentioning
confidence: 99%